Sand wasp (Hymenoptera: Crabronidae) parasites emerging from mud wasp nests (Hymenoptera: Sphecidae)—a reliable host record of Thraxan Yeates & Lambkin (Diptera: Bombyliidae: Anthracinae) with description of the pupal exuviae of three Thraxan species - Li, Xuankun; Yuan, David; Rodriguez, Juanita; Yeates, David K. (Zootaxa, 2019)
Two female Thraxan sp. (Diptera: Bombyliidae: Anthracinae) emerged from parasitised Pison simillimum Smith (Hymenoptera: Crabronidae) larvae found inside a Sceliphron formosum Smith (Hymenoptera: Sphecidae) mud wasps nest. Thraxan sp. larvae are endoparasites of P. simillimum larvae. The endoparasite pupates inside the host larva, kills it, and emerges free of the host body. We describe and illustrate the pupal exuviae of the newly found species and two known species, T. luteus Yeates & Lambkin and T. misatulus Yeates & Lambkin, and we compare these pupal exuviae to those of Anthrax Scopoli.